Earnings volatility in Austria - René Böheim; David Pichler (Johannes Kepler University of Linz, Department of Economics, 2025)
This study analyzes earnings volatility in Austria from 1980 to 2018, providing a comprehensive view of individual income instability and its demographic and structural determinants. Using administrative data, we examine volatility trends by gender, age, earnings deciles, and employment interruptions. We find that earnings volatility has increased over time, with employment interruptions as a major driver, particularly among employees in low-skill sectors and the lower earnings deciles. Additionally, we observe significant gender differences, with women experiencing higher volatility, often linked to childbirth and family-related career interruptions. Through variance decomposition, we attribute the greater share of volatility to demographic changes, including the impact of migration, sectoral shifts, and the growing labor force participation of women.
Keywords: D31; E24; J13; J31; J62; 330; earnings volatility; employment interruptions; labor market dynamics